2007
DOI: 10.1111/j.1751-0813.2007.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Trichostrongylus colubriformis and Haemonchus contortus infections in light bodyweight Merino lambs

Abstract: If the goal is to ensure that lambs develop immunity before weaning, then every endeavour should be made to achieve the combination of critical bodyweight and exposure to moderate levels of nematode infection as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The ability to exclude nematodes from tissues is acquired during the second phase and, in 3-4 month, old, previously naïve 30 kg lambs this occurs after about 8 weeks of infection (Symons et al, 1981;Sykes & Coop, 1976;Kimambo et al, 1988) and, as indicated earlier may be dependent on body maturity (McLure & Emery, 2007).…”
Section: The Immune Response and Productivitymentioning
confidence: 98%
“…The ability to exclude nematodes from tissues is acquired during the second phase and, in 3-4 month, old, previously naïve 30 kg lambs this occurs after about 8 weeks of infection (Symons et al, 1981;Sykes & Coop, 1976;Kimambo et al, 1988) and, as indicated earlier may be dependent on body maturity (McLure & Emery, 2007).…”
Section: The Immune Response and Productivitymentioning
confidence: 98%
“…What is less clear is whether this is an effect of physical age alone or whether it is influenced by stage of maturity and thus an effect of live weight. In one of the few studies to report on the importance of live weight on development of immunity, a minimum weight of 23 kg was required in Merino lambs at the start of infection with T. colubriformis to successfully reduce worm burdens during a secondary infection . Ultimately, age and weight in a growing animal are confounded and it is plausible that age effects on development of immunity reflects the importance of live weight or the stage of their growth trajectory.…”
Section: Factors Influencing the Development Of Immunitymentioning
confidence: 99%
“…A summary of reported mean live weights at the time immunity developed from sources in the literature and estimates of the expected mature weight for each breed are given in Table . In the previously mentioned studies involving a truncated T. colubriformis infection of Merino lambs , an initial live weight of 23 kg was required for lambs to have developed the capacity to limit the size of the parasite burden during a secondary infection, representing an expected relative maturity of 42%. Concurrent decline in FEC and resumption of normal growth indicating immune development and transition to the expression phase in Coopworth lambs has been observed during infection with T. circumcincta or T. colubriformis at relative maturities of 49%, 46% and 44% .…”
Section: Importance Of Relative Maturitymentioning
confidence: 99%
“…In the case of endoparasitism of sheep, a considerable body of work has investigated the interactions between nutrition and resistance, concentrating largely on proteins 7 , 8 , 9 , 10 . Two studies on the effect of age, liveweight and diet on susceptibility of lambs to the gastrointestinal nematode Trichostrongylus ( T. ) colubriformis demonstrated that lambs weighing less than 23 kg at the time of first exposure and thus lacking body reserves have an impaired ability to develop protective gut immunity against a secondary infection 11 unless fed a diet high in total (19.5%) and bypass protein and energy (9.9 MJ metabolizable energy (ME) per kg dry matter) 12 . These studies also found that diets deficient in one of a number of nutrients, including readily available carbohydrate (raCHO), resulted in a reduced (six‐ to ninefold) or retarded resistance of lambs against a secondary infection.…”
mentioning
confidence: 99%